The role of foreign direct investment in the economic development of post-communist transition economies - Zaineb Jalli Alazawi; Moataz Ibrahim Qinbr; Ali Akram Kadhim; Olha V. Izmailova (Encuentros)
Foreign Direct Investment (FDI) has played a crucial role in the growth and advancement of many emerging and developing economies, particularly those recovering from communist rule. This study seeks to determine the influence of foreign direct investment (FDI) on the economic development of nations that underwent a post-communist transition.The current article empirically examines data gathered from many post-communist countries to verify the hypothesized connections between foreign direct investment (FDI) and economic progress.. The results suggest that foreign direct investment (FDI) substantially impacts the economy of these nations by promoting higher levels of investment, job creation, and productivity. Foreign direct investment (FDI) may promote growth by spreading knowledge and facilitating the transfer of technologies. Furthermore, the research emphasizes the importance of institutional quality in attracting foreign direct investment (FDI). This study has two notable implications. At first, it may aid policymakers in countries experiencing a transition after communism in creating favorable conditions for investment, thereby promoting economic growth and attracting foreign direct investment (FDI).